2021
DOI: 10.13057/biodiv/d220845
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellites to reveal genetic diversity and to distinguish four mangoes of Tegal District, Central Java, Indonesia

Abstract: Abstract. Hidayat A, Rahayu ES, Abdullah M, Retnoningsih A. 2021. Microsatellites to reveal genetic diversity and to distinguish four mangoes of Tegal District, Central Java, Indonesia. Biodiversitas 22: 3467-3473. The Wirasangka mango is Tegal District’s flora of identity, which requires recognition, and its existence deserves to be preserved. However, based on the morphology of the fruit, most of the people of Tegal still have difficulty distinguishing the wirasangka mango from other mangoes. Molecular marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(41 reference statements)
1
0
0
Order By: Relevance
“…The overall data (Figure 1 and Table 3) can be described as a total of 52 bands were produced, out of which 28 (53.84%) were polymorphic bands. Generally, the percent of polymorphism reported here was similar to that reported earlier in mangoes by Gitahi et al (2016) and Hidayat et al (2021), but lower than that reported by Surapaneni et al (2013), Zhou et al ( 2020), Anggraheni and Mulyaningsih (2021), He et al (2021) and Srivastav et al (2021). This polymorphism could be the result of replication slippage (Powell et al 1996) or it could be the result of the low genetic stability and high variability of the mango genome in the amplified non-coding regions (Fatima et al 2016).…”
Section: Resultssupporting
confidence: 84%
“…The overall data (Figure 1 and Table 3) can be described as a total of 52 bands were produced, out of which 28 (53.84%) were polymorphic bands. Generally, the percent of polymorphism reported here was similar to that reported earlier in mangoes by Gitahi et al (2016) and Hidayat et al (2021), but lower than that reported by Surapaneni et al (2013), Zhou et al ( 2020), Anggraheni and Mulyaningsih (2021), He et al (2021) and Srivastav et al (2021). This polymorphism could be the result of replication slippage (Powell et al 1996) or it could be the result of the low genetic stability and high variability of the mango genome in the amplified non-coding regions (Fatima et al 2016).…”
Section: Resultssupporting
confidence: 84%